К теории идентификации электромеханических систем энергетическим методом - Родькин, Дмитрий Иосифович; Коренькова, Татьяна Валерьевна; Ковальчук, Виктория Григорьевна (Национальный технический университет "Харьковский политехнический институт", 2019)
Обоснована возможность использования энергетического метода для идентификации параметров электромеханических систем.Показано, что уравнения энергетического баланса мгновенной мощности между источником питания и элементами схемы замещения справедливы для систем любой физической природы, где произведение исходных величин даёт мощность. В основе системы идентификационных уравнений лежат уравнения энергобаланса для отдельных компонент мгновенной мощности между источником и элементами электромеханической системы. Показана возможность применения энергетического метода идентификации параметров в электрогидравлических системах.

The possibility of using the energy method to identification of the electromechanical systems parameters, where the basic theoretical base is the Teljegen theorem, is justified. It is shown that the energy balanceequations of instantaneous power between the power source and elements of the equivalent circuit are valid for systems of any physical nature, where the product of the initial quantities gives power. It is established that the harmonic composition of the power carries certain informational signs characterizing the processes of energy conversion on the electromechanical systems elements. The identification equations system is based on the energy balance equations for the individual components of the instantaneouspower between the source and the electromechanical system elements. Possibleoptions for the formation of input influence in identification systems are given, with which it is possible to obtain significant voltage and current harmonics. The efficiency of the use of the energy method isproved in comparison with the methods based on equivalent resistances of the equivalentcircuit and the balance equations of active and reactive power. The possibility of using the energy method of identifying parameters in electrohydraulic systems is shown, where harmonic analysis of a hydraulic power signal that changes over time allows one to obtain the necessary energy balance equations.
To the theory of electromechanical systems identification by the energy method
Keywords: электромагнитные параметры; мгновенная мощность; уравнения энергобаланса; electromagnetic parameters; instantaneous power; energy balance equations